Metabolic heterogeneous zone assessed by 18FDG‐PET is predictive of postablation mortality in patients with ventricular tachycardia. (1st July 2021) - Miller, Brian; Vunnam, Rama; Mesubi, Olurotimi; Smith, Mark F.; Chen, Wengen; Mahat, Jagat Bandhu; Bentzen, Soren M.; See, Vincent; Restrepo, Alejandro; Shorofsky, Stephen; Dilsizian, Vasken; Dickfeld, Timm‐Michael L.
Abstract: Purpose: We sought to study the predictive value of the metabolic heterogeneous zone (HZ) as determined by 18 Fluorodeoxyglucose ( 18 FDG) positron emission tomography (PET) viability studies in ventricular tachycardia (VT) patients. Methods: PET studies utilizing 82 Rubidium ( 82 Rb) tracer for perfusion and 18 FDG tracer for viability were analyzed using PMOD (PMOD Technologies) and further analyzed using 684‐segment plots. 18 FDG uptake was normalized to the area with maximal perfusion on the rest 82 Rb study. Metabolic scar, HZ, and healthy segments were defined with perfusion‐normalized 18 FDG uptake between 0%–50%, 50%–70%, and >70%, respectively. Results: Thirty‐four VT patients (age, 63 ± 12 years) were evaluated with 18 FDG‐PET viability study. Most ( n  = 31) patients underwent VT ablation. Patients were categorized to HZ < median versus HZ ≥ median based on a median HZ area size of 21.0 cm 2 . HZ size was significantly larger in the deceased group than the alive group (35.2 cm 2 vs. 18.1 cm 2, p  = .01). Deaths were significantly higher in HZ ≥ 21 cm 2 group than HZ < 21 cm 2 group (58.8% vs. 11.8%, p  = .005). Survival analysis showed significantly higher mortality in the HZ ≥ 21 cm 2 group than the HZ < 21 cm 2 group (HR = 4.1, 95% CI: 1.3–12.6, p  = .016). In a multivariable analysis, HZ was found to be an independent predictor for all‐cause mortality (HR = 1.07, 95% CI: 1.02–1.12, p  = .01) Conclusions: Increased HZ size of myocardium was associated with increased mortality. Metabolic HZ quantification may be of value in risk stratification and management of ischemic and nonischemic patients with VT.